Interferon Gamma Release Assays for Diagnosis of Pleural Tuberculosis: a Systematic Review and Meta-Analysis - Aggarwal, Ashutosh N.; Agarwal, Ritesh; Gupta, Dheeraj; Dhooria, Sahajal; Behera, Digambar (Journal of clinical microbiology, 2015)
The role of interferon gamma release assays (IGRAs), although established for identifying latent tuberculosis, is still evolving in the diagnosis of active extrapulmonary tuberculosis. We systematically evaluated the diagnostic performance of blood- and pleural fluid-based IGRAs in tuberculous pleural effusion (TPE). We searched the PubMed and Embase databases for studies evaluating the use of commercially available IGRAs on blood and/or pleural fluid samples for diagnosing TPE. The quality of the studies included was assessed through the QUADAS-2 tool. The pooled estimates of sensitivity and specificity with 95% confidence intervals (95% CI) were generated using a bivariate random-effects model and examined using forest plots and hierarchical summary receiver operating characteristic (HSROC) curves. Indeterminate IGRA results were included for sensitivity calculations. Heterogeneity was explored through subgroup analysis and meta-regression based on prespecified covariates. We identified 19 studies assessing the T.SPOT.TB and/or QuantiFERON assays. There were 20 and 14 evaluations, respectively, of whole-blood and pleural fluid assays, involving 1,085 and 727 subjects, respectively. There was only one good-quality study, and five studies used nonstandard assay thresholds. The pooled sensitivity and specificity for the blood assays were 0.77 (95% CI, 0.71 to 0.83) and 0.71 (95% CI, 0.65 to 0.76), respectively. The pooled sensitivity and specificity for the pleural fluid assays were 0.72 (95% CI, 0.55 to 0.84) and 0.78 (95% CI, 0.65 to 0.87), respectively. There was considerable heterogeneity; however, multivariate meta-regression did not identify any covariate with significant influence. There was no publication bias for blood assays. We conclude that commercial IGRAs, performed either on whole-blood or pleural fluid samples, have poor diagnostic accuracy in patients suspected to have TPE.